2022
DOI: 10.3390/nano12081297
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Doped Carbon Dot/Silver Nanoparticle Nanocomposite-Based Fluorescence Sensor for Metformin Hydrochloride Detection

Abstract: In this study, a fluorescence sensor based on nitrogen and phosphorus co-doped carbon dot/silver nanoparticle (NPCD/AgNP) nanocomposites was developed for metformin hydrochloride (MFH) detection. We first utilized the reducing nature of the NPCDs to prepare AgNPs from Ag+ and subsequently prepare NPCD/AgNP nanocomposites. The nanocomposite material was characterized by various methods, including electron microscopic methods (SEM and TEM), spectroscopic methods (UV-Vis, PL, FTIR, and XPS spectroscopy), light sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…These attributes position them as a promising contender across a spectrum of applications. Because CDs have luminescent properties similar to semiconductor quantum dots [ [16] , [17] , [18] ], resulting in their application across diverse domains, encompassing biomedicine [ 19 ], catalysis, optoelectronic devices and anti-counterfeiting [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These attributes position them as a promising contender across a spectrum of applications. Because CDs have luminescent properties similar to semiconductor quantum dots [ [16] , [17] , [18] ], resulting in their application across diverse domains, encompassing biomedicine [ 19 ], catalysis, optoelectronic devices and anti-counterfeiting [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another contribution, J. Borges et al developed a plasmonic Au-TiO 2 thin film and demonstrated its potential use as an LSPR platform for label-free biosensors [ 6 ]. Fluorescence-based detection is one of main sensing techniques, and S. J Park et al fabricated a nitrogen and phosphorus co-doped carbon dot/silver nanoparticle nanocomposite for a fluorescence sensor, which could sensitively detect metformin hydrochloride with high selectivity [ 7 ]. Efficient pH detection is important in chemical syntheses.…”
mentioning
confidence: 99%